Optimalisasi Pelayanan Pelanggan Pada PT Jasamarga Bali Tol - Winarno, kadek Doni; Putri, I Gst. Agung Pramesti Dwi; Utami, Nengah Widya (AJAD : Jurnal Pengabdian kepada Masyarakat, 2024)
The internship activities carried out at PT Jasamarga Bali Tol aim to gain an in-depth understanding of operational processes and customer service dynamics in the toll road industry. Through direct observation in the field, interviews with various stakeholders, and comprehensive analysis, intern students succeeded in identifying a number of development opportunities that could provide added value to the company. Good observation, communication and analysis skills have enabled intern students to formulate recommendations that are practical and oriented towards improving service quality and company competitiveness. The evaluation results show that the internship activity can be assessed as very good, not only in terms of achieving goals, but also in developing the intern's professional competence. The suggestion put forward is to expand the scope of internship activities to strategic aspects of the company and provide opportunities for intern students to be directly involved in implementing recommendations. Overall, student collaboration can be used as an example of best practice for other companies.